The Customer’s Realization of the Service quality provided by life insurance companies in Baghdad - abdul–kareem, Fa aizah; Al–Qaysi, Bilal Jasim (Opción, 2019)
This study seeks to provide the perspective of clients of life insurance com- panies by providing quality service insurance through six important factors which are (the physical appearance of the office, service performance, service stability, service commitment, understanding of customer needs, customer care). study aims: This study aims to discuss the importance of quality ser- vice insurance and its role in achieving customer satisfaction in light of six important factors selected. Results - I found the study to interact with anyone else in the world. The quality of the insurance service. Design/methodology/ approach - The descriptive approach was used, the questionnaire was used for the purpose of data collection to build a model for the correct and reliable measurement of insurance service quality factors, and the hypotheses were tested through some statistical techniques. Findings : The study reached the agreement of the sample that the most important factor discussed in life in- surance companies from the viewpoint of the sample examined with regard to the quality of the insurance service is (service performance), by providing adequate and adequate material facilities, solving customer problems, and the extent of their impact on the quality Insurance service. Practical implications : This study provides important important factors for the quality of insur- ance services, as it helps managers use them to assess the current situation in the capabilities of insurance companies to perform. Managers may improve their insurance service performance programs more effectively and efficiently through the six factors.Originality/value : This study undertakes to assist service providers in the life insurance sector to address the challenge of increasing service per- formance and achieving customer satisfaction, and how factors of quality service quality affect customer satisfaction.